COMPONENTS OF REPRODUCTIVE ISOLATION BETWEEN ORCHIS MASCULA AND ORCHIS PAUCIFLORA. (29th March 2013) - Scopece, Giovanni; Croce, Antonio; Lexer, Christian; Cozzolino, Salvatore
<x xml:space="preserve">Abstract</x> Studies of the strength and nature of reproductive isolation (RI) between species can greatly contribute to our understanding of speciation. Although the role of RI in speciation is well recognized, there is a dearth of information on the contributions of different barriers between related plant species. Here, we estimated multiple components of RI between two Mediterranean orchid sister species (Orchis mascula and Orchis pauciflora), disentangling the strength and absolute contributions of seven different isolating mechanisms. Our survey includes one prepollination, two postpollination prezygotic (pollen–stigma incompatibility, conspecific pollen precedence), two intrinsic postzygotic (embryo mortality and hybrid sterility) and two extrinsic postzygotic (hybrid habitat differentiation and hybrid pollination) isolating mechanisms. We found strong RI between the investigated species, although none of the barriers were able to completely impede gene flow. Five isolating mechanisms contributed positively to the maintenance of species boundaries. Contrary to most surveys of isolating mechanisms, our data speak against a clear predominance of prepollination or of prezygotic barriers but confirm the emerging pattern of multiple barriers contributing to the maintenance of species integrity. These findings suggest an allopatric condition during early phases of species divergence. We discuss our data in the wider context of previous studies carried out in this orchid group by using a comparative approach.